ANALYZING ENGLISH TEXTBOOKS FOR VOCATIONAL HIGH SCHOOLS IN INDONESIA: A COMPARATIVE STUDY OF 2013 CURRICULUM WITH MERDEKA CURRICULUM - YULIAFNITA, DITA; Perdana, Purnama Rika; Apriyati, Nurul; Cahyani, Nadila Indah (LEAD (Language, Education and Development), 2025)
This study compares the English learning approach in the Merdeka Curriculum and the 2013 Curriculum in Vocational High Schools (SMK). The purpose of this study is to identify the differences in the learning themes and teaching approaches used by the two curricula. The results of the analysis show that the Merdeka Curriculum emphasizes more on real experience-based learning and contextual relevance, with themes that integrate cognitive, affective, and psychomotor aspects. This is in line with the theory of constructivist learning and inquiry-based learning. In contrast, the 2013 curriculum focuses more on developing basic language skills through structured exercises, such as introducing oneself, understanding descriptions of tourist attractions, and telling history and folklore, which reflects more behavioristic learning theories. This study concludes that the Merdeka Curriculum is more appropriate for teaching English in vocational schools because it supports the development of 21st-century skills, such as communication, collaboration, critical thinking, and creativity. Meanwhile, The 2013 Curriculum still has an advantage in building the basics of language skills needed by students. Therefore, it is recommended that elements of practical and collaborative experience be integrated into the 2013 curriculum to create learning that is more holistic and relevant to global challenges.